Calpains promote neutrophil recruitment and bacterial clearance in an acute bacterial peritonitis model. (27th December 2013) - Kumar, Vijay; Everingham, Stephanie; Hall, Christine; Greer, Peter A.; Craig, Andrew W. B.
<x xml:space="preserve">Abstract</x> Activation of the innate immune system is critical for clearance of bacterial pathogens to limit systemic infections and host tissue damage. Here, we report a key role for calpain proteases in bacterial clearance in mice with acute peritonitis. Using transgenic mice expressing Cre recombinase primarily in innate immune cells (fes‐Cre), we generated conditional capns1 knockout mice. Consistent with capns1 being essential for stability and function of the ubiquitous calpains (calpain‐1, calpain‐2), peritoneal cells from these mice had reduced levels of calpain‐2/capns1, and reduced proteolysis of their substrate selenoprotein K. Using an acute bacterial peritonitis model, we observed impaired bacterial killing within the peritoneum and development of bacteremia in calpain knockout mice. These defects correlated with significant reductions in IL‐1α release, neutrophil recruitment, and generation of reactive oxygen species in calpain knockout mice with acute bacterial peritonitis. Peritoneal macrophages from calpain knockout mice infected with enterobacteria ex vivo, were competent in phagocytosis of bacteria, but showed impaired clearance of intracellular bacteria compared with control macrophages. Together, these results implicate calpains as key mediators of effective innate immune responses to acute bacterial infections, to prevent systemic dissemination of bacteria that can lead to sepsis.